2020
DOI: 10.3389/fped.2020.529639
|View full text |Cite
|
Sign up to set email alerts
|

Risk Calculator for Retinopathy of Prematurity Requiring Treatment

Abstract: Importance: Vascular delay that occurs early in the development of retinopathy of prematurity (ROP) is a risk factor that can be compensated by ensuring a good rate of retinal vascularization to avoid ROP that requires treatment. Background: The objective of the present study was to determine the association between ROP that requires treatment and risk factors such as the extent of the temporal avascular area of the retina and the number of days of mechanical ventilation (MV). Design: Observational retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 77 publications
0
22
0
Order By: Relevance
“…The overall knowledge score ranged between 4 and 10, out of a possible maximum of 12 with a mean ± SD of (6.68 ±1.47) and median (IQR) of 7 (6)(7)(8). It was abnormally distributed; the p-value of the Shapiro-Wilk test was 0.043 (Figure 1).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The overall knowledge score ranged between 4 and 10, out of a possible maximum of 12 with a mean ± SD of (6.68 ±1.47) and median (IQR) of 7 (6)(7)(8). It was abnormally distributed; the p-value of the Shapiro-Wilk test was 0.043 (Figure 1).…”
Section: Resultsmentioning
confidence: 98%
“…The extension of the temporal avascular area of the retina should also be considered in the ROP screening of newborns. 2,[6][7][8] Screening preterm infants in the neonatal intensive care unit (NICU) after birth is crucial for ROP prognosis. Therefore, screening guidelines have been implemented to ensure a better outcome for those infants.…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged MV is among the most frequently identified risk factors for ROP [20]. In a Danish study, blood transfusion and MV were the only new risk factors to predict treatment-demanding ROP in addition to GA, SGA, multiple births, and male sex [21].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that low weight is an indicator of the progression of ROP. However, studies have measured the pattern of weight gain (g/kg/day) during the first month of life, and have shown that the use of predictive models that include postnatal weight gain can significantly reduce the number of infants who need to be screened (26) .…”
Section: Discussionmentioning
confidence: 99%